Endogenous neuroprotection: Hamartin modulates an austere approach to staying alive in a recession. Issue 6 (23rd July 2013) - Hadley, Gina; De Luca, Gabriele C.; Papadakis, Michalis; Buchan, Alastair M.
<x xml:space="preserve">Abstract</x> Tuberous sclerosis complex 1 (hamartin) is an effective endogenous neuroprotectant. Understanding the endogenous mechanism for neuroprotection mediated by hamartin may afford a novel approach to effective treatment of neurological diseases such as stroke, neurodegenerative diseases, and epilepsy, with possible applications to nonneurological conditions.